Does Workplace Bullying Produce Employee Voice and Physical Health Issues? Testing the Mediating Role of Emotional Exhaustion - Liang, Huai-Liang (Frontiers in Psychology, 2021)
Workplace bullying is a reality in organizations. Employees’ experiences of workplace bullying can produce their voice, which they use to challenge the status quo, and can damage their physical health. This study examines the effects of workplace bullying on employee voice and physical health issues and considers individuals’ emotional reactions as a critical mechanism operating between workplace bullying and its consequences in workplace situations. Emotional exhaustion mediates the influence of workplace bullying on employee voice and damaged health. Data for 694 employees from a large Taiwanese retail organization revealed that workplace bullying relates to its outcomes at work. The findings of this study show that emotional exhaustion is a critical mechanism between workplace bullying and its consequences, i.e., employee voice and health issues. A time-lag study design is applied to reduce common method bias.